2012
DOI: 10.1002/adfm.201102525
|View full text |Cite
|
Sign up to set email alerts
|

Greener Electrochemical Synthesis of High Quality Graphene Nanosheets Directly from Pencil and its SPR Sensing Application

Abstract: A green, simple, and cost effective electrochemical method to synthesize pure graphene oxide (GO) and graphene nanosheets (GNs) using pencil in ionic liquid medium is reported. The morphology and microstructure of prepared GNs and GO are examined using scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), X‐ray diffraction (XRD), and Raman spectroscopy; the experiments confirm the formation of high quality graphene. The synthesized GO is used for the real‐ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 62 publications
1
83
0
1
Order By: Relevance
“…G band is a signature of true hexagonal carbon rings that arise from in-plane C-C bond-stretching motions, physically corresponding to¯rst-order scattering of the E 2g phonon at the Brillouin zone center and 2D band, which is a frequency dependence of the excitation laser energy corresponds to second-order sp 2 Raman signature by two-phonon scattering processes. [34][35][36][37]46 The high intensity and broadened D and G bands of FLGNs may indicate adequate interaction of Raman signal to small domains of FLGNSs as compared to spectrum in Fig. 5(a).…”
Section: Raman Spectroscopy Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…G band is a signature of true hexagonal carbon rings that arise from in-plane C-C bond-stretching motions, physically corresponding to¯rst-order scattering of the E 2g phonon at the Brillouin zone center and 2D band, which is a frequency dependence of the excitation laser energy corresponds to second-order sp 2 Raman signature by two-phonon scattering processes. [34][35][36][37]46 The high intensity and broadened D and G bands of FLGNs may indicate adequate interaction of Raman signal to small domains of FLGNSs as compared to spectrum in Fig. 5(a).…”
Section: Raman Spectroscopy Analysismentioning
confidence: 93%
“…The strong absorbance peak at 228 nm for both the exfoliated samples is due to -Ã electronic transitions of aromatic C¼C bond present in sp 2 network structure in GO sheets. 37,46 The comparatively higher absorbance in case of Fig. 7(a) is attributed to signi¯cant restoration of carbon aromatic structure at optimum acidic concentration (i.e., 0.5 M H 2 SO 4 ) of electrolytic exfoliation.…”
Section: Uv-visible Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Gr can be obtained from graphite by mechanical cleavage (Jayasena and Subbiah, 2011), chemical exfoliation , thermal decomposition (Wang et al, 2012), or electrochemical exfoliation (Low et al, 2013). Among other methods, electrochemical exfoliation of graphite electrode is considered a simple, rapid, and "green" method, as the use of toxic or corrosive reducing reagents or stabilizers are avoided in this method (Su et al, 2011;Singh et al, 2012;Chang et al, 2013;Gee et al, 2013;Mao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Singh et al demonstrated a green and simple method to synthesis the graphene nano-sheets from a pencil using the electrochemical exfoliation [27]. The bulk charcoal structure in a pencil is confirmed to be similar with graphite that contains multi-layer graphene.…”
Section: Hybrid Mode Locked Fiber Ring Laser Using Charcoal Nano-partmentioning
confidence: 99%